Novel fusion protein REA induces robust prime protection against tuberculosis in mice - Sintayehu Kebede Gurmessa; Han-Gyu Choi; Yong Woo Back; Zongyou Jiang; Thuy An Pham; Seunga Choi; Hwa-Jung Kim (npj Vaccines)
Abstract While many novel candidates for tuberculosis vaccines are presently undergoing pre-clinical or clinical trials, none of them have been able to eliminate infection entirely. In this study, we engineered a potent chimeric protein vaccine candidate, Rv2299cD2D3-ESAT-6-Ag85B (REA), which induced Th1 and Th17 responses via dendritic cell maturation. REA-activated macrophages operated the killing mechanisms of Mycobacterium tuberculosis (MTB), such as phagosomal maturation and phagolysosome fusion, through the (PI3K)–p38 MAPK-Ca2+-NADPH oxidase pathway. Dendritic cells and macrophages activated by REA elicited synergistic anti-mycobacterial responses. Notably, REA-immunized mice suppressed MTB growth to undetectable levels at 16 weeks post-infection, which was supported by gross and pathologic findings and acid-fast staining of the lung tissues, and maintained antigen-specific multifunctional IFN-γ+IL-2+TNF-α CD4+ T and long-lasting T cells producing cytokines in the tissues. Our findings suggest that REA is an outstanding prime prophylactic vaccine candidate against tuberculosis.